2020
DOI: 10.2320/matertrans.mt-m2019152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co and P on the Discontinuous Precipitation Behavior in High Concentration Corson Alloy

Abstract: The effects of Co and P on the discontinuous precipitation (DP) behavior of CuNiSi system alloys have been investigated using Cu4.5 mass%Ni1.1 mass%Si alloy (base alloy), Cu4.0 mass%Ni0.5 mass%Co1.1 mass%Si alloy (Co alloy) and Cu4.0 mass%Ni 0.5 mass%Co1.1 mass%Si0.05 mass%P alloy (Co + P alloy) aged at 430, 460 and 490°C. In all the alloys, slightly before attaining peak agehardening within grains, DP cells nucleated at grain boundaries and grew into the grains ahead of reaction fronts. The growth rates of DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many attempts have been tried for the further improvement in the electrical and mechanical properties of Cu-Ni-Si alloys by the addition of the third trace elements such as Cr, Co, Mg, Al and P to Cu-Ni-Si alloys [9][10][11][12][13]. Thereafter, the effects of these alloying elements on the properties and structure of Cu-Ni-Si alloys have been studied in many previous works [14][15][16]. Trace amount of P can form the Ni 3 P precipitates and suppress the discontinuous precipitation reaction, resulting in enhancement of both strength and elongation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been tried for the further improvement in the electrical and mechanical properties of Cu-Ni-Si alloys by the addition of the third trace elements such as Cr, Co, Mg, Al and P to Cu-Ni-Si alloys [9][10][11][12][13]. Thereafter, the effects of these alloying elements on the properties and structure of Cu-Ni-Si alloys have been studied in many previous works [14][15][16]. Trace amount of P can form the Ni 3 P precipitates and suppress the discontinuous precipitation reaction, resulting in enhancement of both strength and elongation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Alloying is one of the measures to increase strength. It was reported that CuNi Si alloy with the addition of Co and P has high strength due to the discontinuous precipitation after aging treatment 123) and that CuTi alloy with the addition of Mg has higher strength and elongation than CuTi alloy. 124) Also, the treatment of cold-sprayed pure Al substrate and Cu-clad Al wire causes mutual diffusion forming a reaction layer and A d v a n c e V i e w increasing the strength.…”
Section: Conductive Materialsmentioning
confidence: 99%